Prevalence of Depression among the Medical Students in Nepalgunj Medical College - Yadav, Binod Kumar; Shah, Gaurav Jung; Yadav, Rahul; Mahat, Rajendra; Joshi, Aayush (Journal of Nepalgunj Medical College, 2021)
Introduction: Mental health is an important aspect of overall health of a person. Depression is a common mental health problem all around the world. According to WHO, as many as 350 million people suffer from depression all over the globe. Medical studies are well known to be stressful for students and psychological problems like depression are quite common among medical students. Although many studies are done on mental health of students worldwide, studies on depression among medical students of Nepal are quite few. Aims: To find out the prevalence of depression among medical students in Nepalgunj Medical College. Methods: A descriptive study was done in the batch of 2016 with a Beck’s Depression Inventory (BDI) Questionnaire. Results: The prevalence of depression among the study subjects was found to be 25.9%. Bullying was found to be a strong factor responsible for depression among medical students. Conclusion: Depression was highly prevalent among the medical students. Students who were bullied and had appropriate pocket money suffered from higher levels of depression.